The role of time and cost control in CPM, PERT, and EVA methods in construction projects: A meta-analysis study on evaluating project performance - Ramdani, E W P; Tutuko, P; Budiyanto, H; Susanto, Susanto (ASCEE, 2022)
Time and cost efficiency without reducing quality is something that construction service providers always want to achieve in the implementation of project completion. Project work will be limited by cost and time in completion. Methods of controlling time and costs can assist the Project Manager in evaluating project performance and taking actions needed to achieve project objectives. This study is about the comparison of research articles that have been published previously using Meta-Analysis Review which aims to compare three methods that are often used in controlling time and cost, namely CPM (Critical Path Method), PERT Method (Project Evaluation Review Technique), and EVA Method (Earned Value Analysis). The results obtained from the review of this article that each method of controlling costs and time has advantages and disadvantages following their respective characteristics, with that we can know differences of each method. The study found that experience from the Project Manager is needed to choose the right method for implementing project work.